HUKUM SEBAGAI ALAT PENGUBAH MASYARAKAT DAN PENGATUR PERILAKU DALAM PEMBANGUNAN HUKUM EKONOMI DI INDONESIA - Wira Okta Viona (Ensiklopedia Education Review, 2023)
Development aims to change something that doesn't exist yet to exist. What is bad is turned into good, and what is lacking is turned into sufficiency. Development is carried out not only in terms of physical or material, but also build human quality. So, development is not just building buildings, roads, dams, greenery, but building people to be smart, skilled, disciplined, virtuous, and so on. Likewise, the development of Law and Economics is closely related where one influences the other. The history of economic growth and development of law, throughout the world shows that. An economic development will affect the map of law otherwise changes in law will also have a broad impact on the economy. Law and economics are two subsystems of a social system that interact with each other. The purpose of the function of law as a crystallization of the values that grow in the dynamics of society is that the law captures and formulates the aspirations that developed previously in society.